Living territories to transform the world - Caron, Patrick; Valette, Elodie; Wassenaar, Tom; Coppens, d'Eeckenbrugge; Papazian, Vatché (éditions Quae, 2017)
What resources underpin the development of a territory? What does territorial management of resources mean? What specific characteristics and opportunities does territorial organization offer for agricultural production, regulation of sectors, and services? How are territorial public policies conceived and applied? But also, what are the limits of the territorial approach? How does a territorial approach refashion the frameworks of intervention for development? How do we implement and reinvent mechanisms to provide support, build skills, and promote production and good governance? How do we mobilize information systems, apprehend territorial dynamics, and encourage decentralized planning? Using a wide diversity of case studies, the book explores how actors, scales and scopes of intervention interact in the development of rural spaces in the countries of the Global South, both at the local level and in the global perspective of the objectives of sustainable development. The book brings together the experiences and views of more than 150 researchers and experts from CIRAD, AFD and their partners. It is aimed at researchers, engineers, professionals in the countries of the Global South, as well as students and the wider public.